The Elusive Biological Activity of Scorpionates: A Useful Scaffold for Cancer Therapy? - Artem Petrosian; Pedro F. Pinheiro; Ana P. C. Ribeiro; Luísa M. D. R. S. Martins; Gonçalo C. Justino (Molecules, 2024)
Cancer remains a formidable challenge, requiring the constant pursuit of novel therapeutic agents and strategies. Scorpionates, known for their unique coordination properties, have recently gained attention for their anticancer potential. Traditionally applied in catalysis, these compounds have demonstrated notable cytotoxicity across various cancer cell lines, often surpassing the efficacy of conventional chemotherapeutics. This review addresses recent findings on scorpionate complexes, emphasizing the impact of metal choice and ligand design on biological activity. Copper and ruthenium scorpionates show promise, leveraging redox activity and mitochondrial disruption mechanisms to selectively induce cancer cell death. Ligand modifications, including sulfur-containing heterocycles and unsubstituted pyrazoles, have proven effective in enhancing cytotoxicity and selectivity. Furthermore, dipodal ligands show unique potential, with selective binding sites that improve stability and facilitate specific cellular interactions, such as targeting metastatic pathways. These findings highlight the largely unexplored potential of scorpionate complexes, positioning them as candidates for next-generation anticancer therapies. Continued research into structure–activity relationships and precise mechanisms of action could pave the way for developing highly potent and selective anticancer agents based on scorpionate chemistry.